Environmental management accounting, board role performance, company characteristics and environmental performance disclosure - Korutaro Nkundabanyanga, Stephen; Muramuzi, Bruno; Alinda, Kassim (Journal of Accounting & Organizational Change, 2021)
The increasing environmental challenges require efforts to expand the scope of accounting to better evaluate organizations’ behaviour/practices. This paper aims to report the results of studying the link between environmental management accounting (EMA), board role performance (BRP), company characteristics and environmental performance disclosure (EPD) of Ugandan manufacturing firms. Design/methodology/approach – The study was correlational and cross-sectional. The results are obtained through content analysis of company reports, websites and a questionnaire survey of 102 large and medium manufacturing firms in four districts of Uganda. Findings – Results indicate that EMA causes significant variances in EPD in manufacturing firms. Also, BRP and firm size explain variances in EPD through EMA. Research limitations/implications – The research does not control for industry type. Still, the results offer hope on how the reliability of environmental performance information that companies voluntarily provide outside financial statements, can be improved. Originality/value – Results potentially extend available literature by providing a mechanism through which the environmental performance information is obtained for onward disclosure.
Keywords: Disclosure; Firm characteristics; Environmental management accounting; Board role performance